Geography Didactics from the Methodological Guidelines in the USP FFCL Training Course (1934-1960) - Márcia Cristina de Oliveira Mello (2021)
In the previously completed research, "Methodological Guidelines Selected for Geography teachers for the Middle School of the São Paulo School (1934-1960)" stand out the first impressions about the fundamental role that the USP course performed in promoting what we understand nowadays about the practice of teaching geography, especially through the internal organization of Geography Didactics. From the select group of professors graduated from USP's Faculty of Philosophy, Sciences, and Letters (FFCL), between the 1930s and 1960s, a generation of brilliant teaching geographers emerged, among them we highlight, in the continuity of the research, the figure of professor Amélia Americano Domingues de Castro. Professor Amelia was a pioneer in this area and stood out for introducing Jean Piaget's ideas in the initial teacher training course in Geography. Certainly the matrix characterized by the Escanovist orientation of the time had numerous variables, whose versions still need to be investigated in order to understand the present and the multiple anxieties of thinking and how to “do” the teaching of geography in schools. In this sense, we aim to identify and understand aspects of the Geography Didactics constituted in the context of the Escola Nova, from the orientations contained in the USP FFCL Geography Teacher Training Course, expanding knowledge about the contribution of Professor Amelia to Didactics of Geography, in what refers to its scholovist and piagetian matrix through the analysis of the methodological orientations that structured its thinking in articulation with the elements of the pedagogical practice: the student (who learns); the teacher and the geographical knowledge.